10 Watt tv transmitter design: a report on video design for 10 watt transmitter including the following circuit design: clamping, video corrector, clipping and video modulator / Ali R. Ebadi - R. Ebadi, Ali
Listening or hearing, is probably the most informing and pleasing of our five senses. Hearing can be defined and the pleasing of the sound. Sound is the increase and the decrease in air pressure acting on the diaphragm, or drum of the ear. This increase or decrease cause the drum and the inner parts of the ear to vibrate. The action is similar to ripples on the surface of water. Ripples of water develop when a pebble dropped into the pool initially produces a depression within the surface.